Fixed-dose combination of enalapril maleate and hydrochlorothiazide: potential in achieving target blood pressure among hypertensive patients - S. V. Nedogoda; T. A. Chalyabi; U. A. Brel; G. G. Mazina; E. V. Podolskaya; D. A. Zaremba (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To assess the effectiveness of fixed-dose combination of enalapril maleate (20 mg) and hydrochlorothiazide (12,5 mg) - Enap NL 20, comparing to arbitrary combinations of two antihypertensive medications (АНМ), in patients with Stage I-III arterial hypertension (АН) and resistance to previous antihypertensive monotherapy.Material and methods. In 200 patients with high-risk АН and resistance to previous antihypertensive therapy, effectiveness of fixed-dose combination Enap NL 20 and arbitrary АНМ combinations was compared in an open, randomized, controlled parallel-group study Therapy effectiveness was assessed by 24-hour blood pressure monitoring (BPM).Results. Fixed-dose combination Enap NL 20 was more effective than arbitrary combinations of two АНМ for systolic and diastolic BP (SBP, DBP) reduction: -17,3% vs. -10,3% and -13% vs. -5,3%, respectively (p<0,05). Respective pulse BP reduction was 22,6% and 17,3%. T/P index was significantly better in Enap NL 20 patients: 81,2±6,6% vs. 53,1+5,1% in those receiving arbitrary АНМ combinations. Morning SBP surge rate reduction was more pronounced in Enap NL 20 group than in arbitrary АНМ combination group: - 47,7% vs. -19,9% (p<0,05).Conclusion. Enap NL 20 provided better BP control than arbitrary АНМ combinations in patients with high-risk АН and monotherapy resistance. Comparing to arbitrary АНМ combinations, Enap NL 20 more effectively improved 24-hour BPM parameters, also demonstrating better cardio- and angioprotection. Thiazide diuretics in arbitrary АНМ combinations affected the levels of uric acid, creatinine, blood glucose and potassium to greater extent than Enap NL 20.